Multifunctional Yolk‐in‐Shell Nanoparticles for pH‐triggered Drug Release and Imaging. Issue 16 (19th April 2014) - Chen, Hongyu; Qi, Bin; Moore, Thomas; Wang, Fenglin; Colvin, Daniel C.; Sanjeewa, Liurukara D.; Gore, John C.; Hwu, Shiou‐Jyh; Mefford, O. Thompson; Alexis, Frank; Anker, Jeffrey N.
<x xml:space="preserve">Abstract</x> Multifunctional nanoparticles are synthesized for both pH‐triggered drug release and imaging with radioluminescence, upconversion luminescent, and magnetic resonance imaging (MRI). The particles have a yolk‐in‐shell morphology, with a radioluminescent core, an upconverting shell, and a hollow region between the core and shell for loading drugs. They are synthesized by controlled encapsulation of a radioluminescent nanophosphor yolk in a silica shell, partial etching of the yolk in acid, and encapsulation of the silica with an upconverting luminescent shell. Metroxantrone, a chemotherapy drug, was loaded into the hollow space between X‐ray phosphor yolk and up‐conversion phosphor shell through pores in the shell. To encapsulate the drug and control the release rate, the nanoparticles are coated with pH‐responsive biocompatible polyelectrolyte layers of charged hyaluronic acid sodium salt and chitosan. The nanophosphors display bright luminescence under X‐ray, blue light (480 nm), and near infrared light (980 nm). They also served as T1 and T2 MRI contrast agents with relaxivities of 3.5 mM−1 s−1 (r1) and 64 mM−1s−1 (r2). These multifunctional nanocapsules have applications in controlled drug delivery and multimodal imaging.